Enhancing learning management systems towards adaptivity: a case study. (2015) - Skouradaki, Marigianna; Kalogiannakis, Michail; Plexousakis, Dimitrios
Learning management systems (LMSs), enable educators to create a large amount of resources expressed by various technological tools. In this manner, the student is supported throughout the educational process, by interacting with these resources and experiencing an enriched learning process. However, adaptivity and guidance to the student choices are features that seem to be missing from current LMSs. Consequently the students use their own criteria to choose between large collections of resources. As the student abilities are not taken into serious consideration, they are often led to frustration, and wrong choices. This paper focuses on information and communication technologies (ICT) in education. It proposes a prototype that enhances the Moodle LMS's functionality by providing more adaptivity. The goal of this work is to demonstrate an extension of Moodle LMS towards adaptive navigation and student suggestive indications. The resources developed in the framework of this prototype follow the emerging learning theories.